Barcode Order Berbasis Website Guna Memulihkan Ekonomi Umkm Di Masa Pandemi Covid 19 - Ria Manurung; Maria Bellaniar Ismiati (Universitas Katolik Musi Charitas, 2022)
The current state of Indonesia, which is still experiencing bad conditions caused by the Covid-19 virus, has made the government issue a policy to stop the spread of this virus with physical distancing to avoid crowds. This also affects the culinary business at Cafe Radio Kopi Gombong, where orders are still done manually, which requires a waiter to come to the consumer's table to choose the menu. Then with the Contactless Order System on the Website-based Coffee Radio, it is able to reduce contact with people, consumers who come to the coffee radio can directly order menus by logging into the ordering web using a barcode through the consumers' own gadgets. The system development method used is the prototype method with the help of the PHP programming language and the CodeIgniter framework. The results of this study concluded that there was an increase in the efficiency of ordering that occurred at the Radio Kopi Gombong cafe.